Leisure time physical inactivity and self-perception of health status in Colombian adults from 18 to 64 years old (2017)
Objective: To explore the relationship between leisure time physical inactivity (PI) and self-perceived health status in the Colombian population between 18 and 64 years of age reported in the National Nutrition Situation Survey (ENSIN) and National Demography and Health Survey (ENDS) 2010. Methods: Cross-sectional analytical study to explore the association between physical inactivity and self-perception of the health status of Colombians between 18 and 64 from the National Survey of Nutrition Situation in Colombia (ENSIN) and the National Demographic and Health Survey (ENDS) 2010. Results: PI explains a regular and poor self-perception of health (0R= 1.37; IC95% 1.10-1.70) in women after adjusting for confounding factors. Other associated variables included: age, educational level, affiliation to the health system, marital status, living in eastern region and Bogota. PI was not associated with self-perception of health status In men (0R=1.04; IC95% 0.85-1.29), but age and low educational level did show association. Conclusion: Low levels of leisure time physical activity were associated with regular and poor self-perceived health status in women, whereas in men this relationship was not observed.